Elementary Students’ Needs for Interactive Cultural Learning Media: A Needs Analysis for an AR-Based Game - Arum Astiningati; Putri Rachmadyanti; Nasution Nasution (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study analyzes the empirical needs for developing augmented Reality (AR)-based game learning media integrated with local wisdom to support cultural Learning in Integrated Science and Social Studies at the elementary level. Using a qualitative case study within a needs analysis framework, the study involved 28 fifth-grade students and 3 teachers. Data were collected through in-depth interviews, four-point Likert-scale questionnaires, and structured classroom observations, and were analyzed thematically through triangulation. The findings reveal three key gaps. Cultural learning remains dominated by teacher-centered instruction and limited interactive media (M=2.1). Students show strong preferences for visual media (M=3.7) and game-based Learning (M=3.6). Their knowledge of local cultural heritage is still low (M=1.9). Teachers also expressed positive views on integrating game mechanics and AR, though technical readiness remains a constraint. Overall, the findings provide an empirical basis for developing contextual, interactive, and culturally relevant AR Monopoly media to improve literacy, Engagement, and cultural understanding in digital learning environments.